Colonic Occlusion by Gall Stone - Burstin, Jacobo; Dorf, Jaime (Cirugía del Uruguay, 1981)
Description of a case of occlusion of descending colon which was due to gall stone. The calculus was of customary size and colon had presented no previous pathology,